The long-term variation of Cd and Zn hyperaccumulation by Noccaea spp and Arabidopsis halleri plants in both pot and field conditions - Tlustoš, Pavel; Břendová, Kateřina; Száková, Jiřina; Najmanová, Jana; Koubová, Kateřina (International journal of phytoremediation, 2016)
Three Cd and Zn hyperaccumulating plant species Noccaea caerulescens Noccaea praecox and Arabidopsis halleri (Brassicacceae) were cultivated in seven subsequent vegetation seasons in both pot and field conditions in soil highly contaminated with Cd, Pb, and Zn. The results confirmed the hyperaccumulation ability of both plant species, although A. halleri showed lower Cd uptake compared to N. caerulescens. Conversely, Pb phytoextraction was negligible for both species in this case. Because of the high variability in plant yield and element contents in the aboveground biomass of plants, great variation in Cd and Zn accumulation was observed during the experiment. The extraction ability in field conditions varied in the case of Cd from 0.2 to 2.9 kg ha(-1) (N. caerulescens) and up to 0.15 kg ha(-1) (A. halleri), and in the case of Zn from 0.2 to 6.4 kg ha(-1) (N. caerulescens) and up to 13.8 kg.ha(-1) (A. halleri). Taking into account the 20 cm root zone of the soil, the plants were able to extract up to 4.1% Cd and 0.2% Zn in one season. However, cropping measures should be optimized to improve and stabilize the long-term phytoextraction potential of these plants.
Keywords: Arabidopsis; Soil Pollutants; kadmium; druhová specificita; roční období; Biodegradation, Environmental; Cadmium; látky znečišťující půdu; biodegradace; hyperaccumulator; Species Specificity; zinek; Plant Roots; Seasons; cadmium; Brassicacceae; kořeny rostlin; phytoextraction; zinc; Zinc; Brassicaceae